Consciousness level monitoring using biespectral index and spectrogram in a patient with locked-in syndrome under general anesthesia: a case report (Research, Society and Development, 2023)
Introduction: Locked-in syndrome is a neurological condition in which the patient develops tetraplegia and anarthria, becoming unable to perform limb movements and speak, however, maintains proprioception and consciousness, in addition to vertical eye movement, which is the main only way for the patient to communicate. Among the various types of intraoperative monitoring, the BIS and the spectrogram provide us with the analysis of the patient's level of consciousness, allowing the maintenance of an adequate anesthetic plane, reducing intraoperative awakening and the complications of a very deep anesthetic plane. Objective: To describe a case of a patient who developed locked-in syndrome due to a pons ischemic stroke and underwent general anesthesia with monitoring of the level of consciousness with the bispectral index (BIS) and spectrogram. Case report: A 50-year-old female patient, housewife, was admitted to the emergency room at UPA São Sebastião - Brasília DF, with a condition of lowered level of consciousness. Daughter reports that the patient complained of severe headache, followed by syncope. She was evaluated by the medical team, who opted for orotracheal intubation and transferred her to a reference service in neurology due to the suspicion of stroke. Conclusion: Despite the apparent state of coma, the patient with locked-in syndrome presents data from monitoring of anesthetic depth with BIS and spectrogram similar to the normal population, which makes its use important in the prevention of negative outcomes, such as intraoperative awareness.